Forum Demokrasi (Democratic Forum): An Intellectuals’ Responses to the State and Political Islam - SRS., Herdi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Indonesian political life are colored appearance of intellectual religious organizations. Listed first is the Association of Indonesian Muslim Intellectuals (ICMI), which was established in 1990. Following years formed the Indonesian Hindu Intellectuals Forum (FCHI) and the Indonesian Buddhist Scholars Family (KCBI). While the Association of Indonesian Christian Intelligentsia (PIKI) and the Indonesian Catholic Scholars Association (ISKA), each of which stands in 1963 and 1958, re-grown, along with the others.Among these organizations, ICMI is a religious organization-the most prominent scholars. Most of his followers and their role in political life is crucial. A large number of its members supported the fact that the majority of Indonesian Muslims. While the success of ICMI more possible role of elite countries that provide full support. The bureaucrats, ranging from ministerial level to local officials, many who take charge of ICMI. Even the chairman of ICMI itself is B.J. Habibie, who was then serving as Minister of Research and Technology.DOI: 10.15408/sdi.v2i4.825